1988
DOI: 10.1111/j.1469-8137.1988.tb04206.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of lichens to salinity: concentration and time‐course relationships and variability among Californian species

Abstract: S L-M . M .\ R "t'Sensitivity to salinity varied widely among 12 Californian lichen species occurring along a coastal to inland gradient, with the degree of sensitivity being approximately proportional to the distance from the coast where the species grew. For four of the.se species, it was found that net photo.synthesis in three decreased with increasing seasalt concentrations, but in Deiidrographa minor Darh. it was essentially unaffected. Time-course studies with Fseudocypheltaria niwiiiata Magn., a sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 24 publications
2
19
0
1
Order By: Relevance
“…-4 MPa, net photosynthesis was decreased to zero in sea salt, whereas the same water potential permitted more than 75% of the control rate of net photosynthesis under osmotic (sorbitol) stress or atmospheric desiccation. In agreement with our earlier findings (Nash & Lange, 1988), the photosynthetic apparatus of this species exhibited a specific ion sensitivity, which is consistent with its restriction to habitats far from the infiuence of the coastal salt spray.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…-4 MPa, net photosynthesis was decreased to zero in sea salt, whereas the same water potential permitted more than 75% of the control rate of net photosynthesis under osmotic (sorbitol) stress or atmospheric desiccation. In agreement with our earlier findings (Nash & Lange, 1988), the photosynthetic apparatus of this species exhibited a specific ion sensitivity, which is consistent with its restriction to habitats far from the infiuence of the coastal salt spray.…”
Section: Discussionsupporting
confidence: 92%
“…During the measurement period of 2-5 to 3 h, the lichen samples remained wetted with the treatment solution. Previous studies had established that no further decline in gas exchange rates occurred subsequent to the exposure to salt solutions over this period of time (Nash & Lange, 1988).…”
Section: Pre-experimental Conditionsmentioning
confidence: 72%
See 1 more Smart Citation
“…Matthes-Sears et al (1987) showed that in R. menziesii overall photosynthesis rates were unaffected by intrathallus Na^ levels; they speculated that the primary physiological effect of NaCl was osmotic dehydration. In contrast, Nash & Lange (1988) demonstrated that different lichen species responded differently to sorbitol, sea salt, and NaCl. Broader studies are needed in which osmotic, matric, and salt stresses are compared.…”
Section: Discussionmentioning
confidence: 93%
“…The negative correlation of lichen richness and rock exposure may be related to the fact that areas of bedrock contained few shrubs and trees and therefore little habitat for the potential suite of epiphytic species. Although lichens exhibit a wide range of salt tolerance (Nash and Lange 1988), higher lichen richness in areas further from the coast and correspondingly lower in salinity may indicate that the majority of barrens macrolichens are salt-sensitive.…”
Section: Conservation Strategiesmentioning
confidence: 98%